Polyfunctional cytomegalovirus-specific CD4+ and pp65 CD8+ T cells protect against high-level replication after liver transplantation. - Nebbia, G; Mattes, F; Smith, C; Hainsworth, E; Kopycinski, J; Burroughs, A; Griffiths, P; Klenerman, P; Emery, VC (2008)
To determine whether polyfunctional CD4+ T-cell responses coupled with CD8+ T-cell responses against human cytomegalovirus (HCMV) are key to the control of HCMV replication we prospectively analyzed 29 liver transplant recipients for CD4+ T-cell responses against soluble HCMV antigen, pp65 and IE1 proteins, CD8+ T-cell responses against pp65 and IE1 proteins and a range of T helper (Th) 1 and Th2 cytokines. Eleven patients (38%) developed HCMV DNAemia at a median of 21 days post-liver transplantation (range 17-31 days). There was a significantly lower frequency and absolute number of total HCMV CD4+ T cells producing IFNgamma, IFNgamma+IL2 and IL2 and pp65-CD8+ T cells producing IFNgamma in patients with DNAemia. The quantities of Th1 and Th2 cytokines present during the first 20 days posttransplant were not predictive of DNAemia. Cut-off levels during the first 20 days posttransplant of 0.1% of lysate stimulated CD4+ T cells producing IL2, and pp65-CD8+ T cells producing IFNgamma above 0.4% had positive and negative predictive values for DNAemia of 54% and 100% and 50% and 92%, respectively. Measuring polyfunctional CD4+ T cells against HCMV early posttransplant may allow targeted intervention to minimize the occurrence and acute and long-term consequences of HCMV replication.